History of blood pressure measurement in newborns and infants - Javorka, Kamil (Physiological research, 2023)
The development of methods for measuring blood pressure (BP) in newborns and small children has a rich history. Methods for BP measuring in adults had to be adapted to this age group. For measuring BP in direct invasive way, a suitable approach had to be found to access the arterial circulation through the umbilical and later radialis artery. Currently, results obtained from direct invasive BP measurement are considered the "gold standard". The development of non-invasive methods for BP measuring in newborns and children began with the use of von Basch's sphygmomanometer (1880). In 1899, Gustav Gärtner constructed the device, which was the basis for the flush method. After the discovery of the palpation and auscultation methods, these methods were also used for BP measurement in newborns and children, however, the BP values obtained in these ways were typically underestimated using excessively wide cuffs. From the auscultation method, methods utilizing ultrasound and infrasound to detect arterial wall movement and blood flow were later developed. The oscillometric method for BP measurement was introduced by E. J. Marey so early as in 1876. In 1912, P. Balard used the oscillometric technique to measure blood pressure in a large group of newborns. Through different types of oscillometers using various methods for detecting vascular oscillations (such as xylol method, impedance and volume plethysmography, etc.), the development has continued to assessment of vascular oscillations by modern sensor technology and software. For continuous non-invasive blood pressure measurement, the volume-clamp method, first described by Jan Peňáz in 1968, was developed. After modification for use in newborns, application of the cuff to the wrist instead of the finger, it is primarily used in clinical physiological studies to evaluate beat-to-beat BP and heart rate pressure variability, such as in the determination of the baroreflex sensitivity.
Keywords: novorozenec; Infant, Newborn; Infant; Humans; kojenec; Blood Pressure Determination; dítě; Child; Fingers; dospělí; lidé; Adult; arterie; arteriální tlak; Arteries; krevní tlak; prsty ruky; Arterial Pressure; Blood Pressure; měření krevního tlaku